Clinical case of urgent hybrid cardiosurgical intervention in patient with acute myocardial infarction complicated acute mitral insufficiency - S. V. Salo; V. I. Ursulenko; S. O. Siromakha; A. A. Berogovoy; A. Yu. Gavrylyshyn (Ukrainian Journal of Cardiovascular Surgery, 2016)
The article describes the case of mechanical complication of acute myocardial infarction – acute mitral regurgitation, which required the use of hybrid treatment (surgical and endovascular) using mechanical support, which is of interest given the complexity of the case and the choice of surgical treatment.